2021
DOI: 10.1002/pc.26103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coir fiber and inorganic filler on physical and mechanical properties of epoxy based hybrid composites

Abstract: The present work's target is to study the impact of fly ash or TiC nanoparticles or both on the characteristics of coir fiber epoxy hybrid composites. Mechanical characteristics like tensile, flexural, inter-laminar shear strength, impact strength, shore D hardness, and thermal stability or degradation characteristics were determined. The microstructure of the samples was observed from a scanning electron microscopy. It was observed that the addition of coir fiber, fly ash, and TiC nanoparticles in the epoxy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 70 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The transparency setting was used to capture the FTIR spectrum. Figure 3 widened, perhaps due to interactions of hydrogen bonds among SiO 2 nanoparticles and PALF ber [23].…”
Section: Ftir Characterizationmentioning
confidence: 99%
“…The transparency setting was used to capture the FTIR spectrum. Figure 3 widened, perhaps due to interactions of hydrogen bonds among SiO 2 nanoparticles and PALF ber [23].…”
Section: Ftir Characterizationmentioning
confidence: 99%
“…The TGA curves show similar trends for all the composites which signifies that addition of HGMs to coir/epoxy composite does not appreciably affect their thermal stability (Figure 5D). Kavya et al 44 also observed that the thermal properties of coir fiber epoxy composite was not significantly changed due to incorporation of inorganic fillers. In another study, thermal property of the composites was insignificantly varied with varying weight percentages of reinforcements 45 .…”
Section: Resultsmentioning
confidence: 98%
“…The orientation and plastic flow of the HDPE were observed in the few composite places. [63][64][65] Because the polar groups in CC resisted the nonpolar groups in HDPE, the CC particles were not evenly distributed throughout the HDPE matrix and were separated from it. The dispersion might be enhanced even further by lowering the size of the fillers.…”
Section: Scanning Electron Microscopy (Sem) Studiesmentioning
confidence: 99%